The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.4317/medoral.21755
|View full text |Cite
|
Sign up to set email alerts
|

Oral and oropharyngeal squamous cell carcinoma in young adults: A retrospective study in Granada University Hospital

Abstract: BackgroundThis study aims to evaluate and analyze the clinical features and outcomes of oral and oropharyngeal squamous cell carcinoma (SCC) in patients < 45-years old in our center.Material and MethodsA retrospective analysis was conducted using the records of patients diagnosed with oral and oropharyngeal SCC between 1998 and 2011 in the University Hospital of Granada (Spain). The analysis identified 33 patients with oral and oropharyngeal SCC with an age of <45 years. Moreover, during the years studied, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…A review of the reported studies demonstrates that our clinical characteristic findings are in agreement with several previously published large cohort studies [12][13][14][15][16][17][18][19]. First, OC-SCC mainly occurs in men between the 5th and 6th decades of life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A review of the reported studies demonstrates that our clinical characteristic findings are in agreement with several previously published large cohort studies [12][13][14][15][16][17][18][19]. First, OC-SCC mainly occurs in men between the 5th and 6th decades of life.…”
Section: Discussionsupporting
confidence: 91%
“…In many types of cancer, age at diagnosis is viewed as an independent predictor of outcome [11]. In the field of OC-SCC, there is no uniform category of "young" patients and previous analyses were performed using age thresholds ranging from 30 to 45 years of age [12][13][14][15][16][17][18][19]. It is difficult to determine a reasonable cutoff between "young" and "old" adults.…”
Section: Discussionmentioning
confidence: 99%
“…Cariati et al 16 compared 33 patients with oral and oropharyngeal SCC who were 45 years old or younger with 100 patients older than 45. While the oral tongue was the most common subsite, in the young group, the proportion of oral tongue cancer among young patients was less than that shown in our cohort (54.5%, 18/33).…”
Section: Discussionmentioning
confidence: 99%
“…Squamous Cell Carcinoma (SCC) of the head and neck regions represents the sixth most common cancer in male patients after lung, prostate, colorectal, stomach, and bladder cancer; but the tenth most common cancer in female patients after breast, colorectal, lung, stomach, uterus, cervix, ovary, bladder and liver cancer [1][2][3][4]. It is usually encountered during the sixth and seventh decades of life, but the increase of patients under the fifth decade was recently reported in the literature [3]. Squamous Cell Carcinoma (SCC) is considered the most common malignant tumor of the oral cavity [1,[5][6][7] that represents approximately 90-95% of all oral malignant tumors [4,7].…”
Section: Interoductionmentioning
confidence: 99%
“…At least half of the head and neck malignant tumors reported in the literature are oral SCC [1]. The SCC of the palate as well as SCC of maxillary gingiva and maxillary alveolus are relatively rare compared to other sites of oral SCC [1,3,5,6,8]. SCC accounts for 66% of malignant tumors of the hard palate and maxillary alveolus.…”
Section: Interoductionmentioning
confidence: 99%